2007
DOI: 10.1007/s10661-007-9649-7
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of environmental parameters for CO2 sequestration: a case study of Nagpur City, India

Abstract: Carbon dioxide concentration is an index of total amount of combustion and natural ventilation in an urban environment and therefore required more careful attention for assessment of CO(2) level in air environment. An attempt was made to monitor CO(2) levels in ambient air of Nagpur city at industrial, commercial and residential sites. In addition to this a remote sensing studies and biotic survey for floral biodiversity were carried out to study the green cover at respective sampling locations. The observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Guoke et al (2009) examined detectability of six shrub and tree species in 20 × 20-m plots, and found that detectability ranged from 0.09 to 0.24 on average. These findings contrast with the assumption of many conventional flora surveys, that the majority of persistent vegetation species are highly or perfectly detected (for example, Chaudhari et al 2007). We and others believe that this assumption is drawn from the simple but flawed logic that due to their sedentary nature, plants are easier to detect than animals (Slade et al 2003).…”
Section: Introductionmentioning
confidence: 60%
“…Guoke et al (2009) examined detectability of six shrub and tree species in 20 × 20-m plots, and found that detectability ranged from 0.09 to 0.24 on average. These findings contrast with the assumption of many conventional flora surveys, that the majority of persistent vegetation species are highly or perfectly detected (for example, Chaudhari et al 2007). We and others believe that this assumption is drawn from the simple but flawed logic that due to their sedentary nature, plants are easier to detect than animals (Slade et al 2003).…”
Section: Introductionmentioning
confidence: 60%
“…Idso et al (2002) also reported a marginal difference in CO 2 concentrations between the urban and sub urban sites during the morning time and high difference during the night time. In addition, several other studies reported the presence of higher CO 2 concentrations at urban sites than at the background or rural sites (George et al, 2007;Idso et al, 2001;Gratani and Varone, 2005;Henninger and Kuttler, 2010;Rice and Bostrom, 2011;García et al, 2012;Chaudhari et al, 2007;Büns and Kuttler, 2012;Briber et al, 2013). Table 2 shows the intensity of CO 2 domes in various cities across the world.…”
Section: Comparison Of Co 2 Concentrations In Different Land Usesmentioning
confidence: 99%
“…We saw a drop in the CO 2 mixing ratio during the rainfall period due to changes in various processes, such as enhanced vertical mixing, uptake of CO 2 by vegetation and soils, and, where relevant, reduction in combustion sources. CO 2 can also dissolve into rainfall, forming carbonic acid, which may lead to a small decrease in the CO 2 mixing ratio as has been observed during high-intensity rain- fall (Chaudhari et al, 2007;Mahesh et al, 2014). The monsoon is also the growing season with higher CO 2 assimilation by plants than in other seasons (Sreenivas et al, 2016).…”
Section: Monthly and Seasonal Variationsmentioning
confidence: 93%